Dispositional Mental States of Internally Displaced University Teachers Under Martial Law: Gender Differences - Popovych, Ihor; Hudimova, Alisar; Bokhonkova, Yulia; Savchuk, Oleksandr; Hoian, Ihor; Shevchenko, Nataliia (Journal of Education Culture and Society, 2023)
Aim. The empirical study of gender differences in the dispositional mental states of university teachers who were internally displaced during martial law.Methods. A combined research strategy was used, integrating the methods for comparing samples of female and male participants. The different types of dispositional mental states of the respondents were identified by the author’s methodology for the study of dominant mental states.Results. It was discovered that the respondents’ psychological content parameters showed statistically significant gender-based differences. Group 1 prevailed in terms of anxiety (U = 855.0; p = .000). Group 2 prevailed in terms of self-control (U = 975.0; p = .001); awareness of events (U = 707.5; p = .000); expected attitude (U = 1074.0; p = .006); expected result (U = 1067.0; p = .006) and psychological well-being (U = 1113.5; p = .014). The dispositional mental states of a female sample of internally displaced university teachers were represented by five components with a total variation of ∑d = 74.527%. The male sample had four factors with a total variation ∑d = 94.442%. It was stated that there were significant differences between the dispositional mental states of female and male teachers in terms of formal characteristics and content loading of components.Conclusions. The scientific value of empirical facts about the dispositional mental states of university teachers who were internally displaced as a result of wartime action is justified. The importance of incorporating the discovered results into scientific and educational processes is emphasised.